Booker T. Washington Papers Volume 2 : 1860-89. Assistant editors, Pete Daniel, Stuart B. Kaufman, Raymond W. Smock, and William M. Welty - Washington, Booker T., 1856-1915 (Book collections on Project MUSE., 2015)
In his lifetime Washington was the most influential African American in the United States. In this volume the editors hope to convey the shaping forces of his early life. They have gathered and annotated more than 400 documents, including letters, speeches, articles, and other writings from shortly after Washington's birth in 1856 to the death of his second wife in 1889. Much of the material relates to the founding of Tuskegee Normal and Industrial Institute. Washington's life became so interwoven with his school that to illustrate his career is also to tell the story of the institution.